Evaluasi Lapang dan Identifikasi Molekuler Plasma Nutfah Padi terhadap Keracunan Fe - Dwinita W. Utami; Ida Hanarida (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
Fe toxicity is one of the abiotic constraints thatcan significantly decrease rice production, especially inmarginal wetlands. The use of tolerant varieties can reducethe cost of soil processing and fertilizing. Many accessions ofrice germplasm have potential alleles that can be utilized tocreate new varieties tolerant to Fe toxicity. The objectives ofthis research were to evaluate the Fe toxicity tolerance ofrice germplasm and to analyze the genotype diversity usingSNP markers for OsIRT, Fe toxicity tolerant gene(s). Fetoxicity tolerant rice germplasms were screened in acidmarginal wetlands of Taman Bogo Experimental Station,Indonesian Soil Research Insitute, Lampung Province.Meanwhile, the genotypes performance analysis wasconducted on SNP genotyping analysis using SNP markersfor OsIRT gene(s). Based on phenotypic data of 97accessions, which were clustered into six groups, two ofthem (group 2 and group 5) consisted of the tolerantaccessions at both vegetative and generative stages. Theresults of grouping analysis of genotyping based on SNPmarkers were obtained that there were five genotypegroups: AGT, AAT, GAT, AAC, and GAC. The AGT genotypecluster was dominated by the accessions included in group1. Meanwhile, the GAT genotype cluster consisted of mixedtolerant and untolerant accessions to Fe toxicity. The GACgenotype cluster was dominated by the accessions includedin group 2. The accessions which were included in the besttolerant group, group 5, were separated in differentgenotype cluster. Based on association analysis, among thethree SNP markers, OsIRT1 was the most significant SNPmarker (P value = 0.01) which correlated to Fe toxicitytolerant on vegetative stage. Some of the selectedaccessions that were tolerant to Fe toxicity and had goodagronomic performance on acid soil with high Fe contentwere Ketan Alay, Markuti, Arias Halus, Komas a, Lantiak,and Utri Deli. These local rice accessions have the potentialalleles of OsIRT genes.